Performance evaluation of trimethylamine–carbon dioxide thermolytic draw solution for engineered osmosis - Boo, C; Khalil, Y; Elimelech, M (Elsevier, 2014)
We evaluated the performance of trimethylamine–carbon dioxide (TMA–CO2) as a potential thermolytic draw solution for engineered osmosis. Water flux and reverse solute flux with TMA–CO2 draw solution were measured in forward osmosis (FO) and pressure retarded osmosis (PRO) modes using thin-film composite (TFC) and cellulose triacetate (CTA) FO membranes. Water flux with the TMA–CO2 draw solution was comparable to that obtained with the more common ammonia–carbon dioxide (NH3–CO2) thermolytic draw solution at similar (1 M) concentration. Using a TFC–FO membrane, the water fluxes produced by 1 M TMA–CO2 and NH3–CO2 draw solutions with a DI water feed were, respectively, 33.4 and 35.6 L m−2 h−1 in PRO mode and 14.5 and 15.2 L m−2 h−1 in FO mode. Reverse draw permeation of TMA–CO2 was relatively low compared to NH3–CO2, ranging from 0.1 to 0.2 mol m−2 h−1 in all experiments, due to the larger molecular size of TMA. Thermal separation and recovery efficiency for TMA–CO2 was compared to NH3–CO2 by modeling low-temperature vacuum distillation utilizing low-grade heat sources. We also discuss possible challenges in the use TMA–CO2, including potential adverse impact on human health and environments